Handling tradition for a systemic innovation - Voyatzaki, Maria (Journal of Architecture and Urbanism, 2013)
There is always something from the past embedded in the new, establishing a synergetic and sympathetic relationship which gives meaning and value to this new creation. Innovation is about creating new values. Contemporary trends in architectural contemplation and creation are looking into a redefinition of innovation as an inventive systemic synergy of multiple parameters, the dynamic modeling of which, with the aid of new digital technologies, can suggest the appropriate form and materiality of architectural design. Sympathy and synergy are not mere situations, but primarily values that nurture architectural design and open up new challenges for architectural education. Materialised architecture is the expression of worldviews and values. Its form and materiality constitute the meaningful platform on which the relationship between tradition and innovation are represented. Tradition and innovation have always been in a binary opposition. Through the act of creation, invention, innovation, change and transformation are introduced. However, there has always been something in the new that comes from the existent. This condition can become the foundation for a new conception of innovation to emerge, a systemic innovation in which tradition is reflected upon and exploited as a constraint that will leverage and foster it.